The art of talking with children : the simple keys to nurturing kindness, creativity, and confidence in kids - Rolland, Rebecca (HarperOne, an imprint of HarperCollinsPublishers, 2022)
A Harvard faculty member and oral language specialist provides adults with evidence-based tools and techniques to help them have productive and meaningful conversations with children of all ages.